Роль социальных сетей в виртуальном и реальном мире - Байбак, И. А. (ХНУРЭ, 2012)
The given article is devoted to the problem of the social nets. The author have analyzed the role of social nets in life and work of the modern humanity. Especially attention was given to the possibilities of social nets for whole society.